Anti-Inflammatory and Anti-Arthritic Potential of Standardized Extract of Clerodendrum serratum (L.) Moon - Tiwari, Raj Kumar; Chanda, Silpi; M, Udayabanu; Singh, Manisha; Agarwal, Shriya (Frontiers in Pharmacology, 2021)
Aims: Scientific biological evaluation of standardized extract is becoming one of the central necessity for globalization of customary medication in the cutting edge time. And to validate the presence of active constituents in crude medicinal extracts, analytical techniques like HPLC, HPTLC are the most suitable authetication system. In the current study we aimed to standardize and evaluate Clerodendrum serratum (L.) Moon (Verbenaceae). for its unique benefit to medicinal property as anti-inflammatory and anti-arthritic. Evaluation and analysis of plant, therefore, offer a new platform for the development of herbal drug and can serve as a key role in the safety and cost effective especially in the area of arthritis management. Methods: The aqueous extract of C. serratum, one of customary plant of the southeastern Asian region was used for phytochemical investigation and standardization by HPTLC and HPLC. The standardized HPLC method was further validated by using ICH guidelines. The stardadized extract was investigated for anti-inflammatory and anti-arthritic activity. Complete Freund’s adjuvant (CFA) model was performed to evaluate the activity. Paw diameter, joint diameter, arthritic score, and body weight was accepted as a parameter for the evaluation of biological activity. Results: HPTLC method revealed the presence of ursolic acid with Rf value of 0.38 and amount quantified was 0.03% w/w. The presence the bioactive phytochemical is further analysed and confirmed by HPLC for which the validation was done successfully in accordance with ICH guidelines. The assay content for ursolic acid was found to be 0.059% with relative standard deviation (RSD) <2.5% for specificity and precision with spike recovery between 95-110%. The anti-arthritic activity of aqueous extract exhibited COX-2 and TNF-α inhibition as observed in various parameters like paw edema, arthritic index and joint diameter. Plant extract showed reclamation of arthritis in regard to body weight, arthritic score, paw edema and joint diameter. The extract showed significant result for TNF-α and COX-2(P < 0.0001). The plant extract also exhibited in-vitro anti-inflammatory activity. Conclusions : The current study established the scientific basis of ethnomedicinal use of the plant for anti-inflammatory and arthritis and can also be used for quality control purpose.